2019
DOI: 10.32502/sm.v8i1.1359
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Curah Hujan, Suhu, Kelembaban dengan Kasus Demam Berdarah Dengue di Kota Semarang

Abstract: DBD merupakan salah satu masalah kesehatan masyarakat yang terjadi di Indonesia, khususnya Kota Semarang. Angka kejadian DBD di Kota Semarang menduduki urutan pertama di Jawa Tengah pada Tahun 2014 sejumlah 11.081 kasus. Munculnya angka tersebut dipengaruhi oleh faktor-faktor seperti curah hujan, suhu dan kelembaban. Penelitian ini bertujuan mengetahui hubungan antara curah hujan, suhu dan kelembaban dengan jumlah kasus DBD di Kota Semarang. Penelitian deskriptif analitik secara retrospektif dengan rancangan c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Based on research conducted many factors that influence the disease DHF, this is supported by secondary data obtained in each research area. Rainfall, Temperature, and Humidity are physical factors that affect DHF, this was conveyed in the study [21] by taking secondary data in Semarang City in 2006 -2015 it was found that rainfall, temperature, and humidity had an effect on the number of DHF cases in Semarang. Semarang City (p < 0.05).…”
Section: Factors That Affect Dhfmentioning
confidence: 90%
See 2 more Smart Citations
“…Based on research conducted many factors that influence the disease DHF, this is supported by secondary data obtained in each research area. Rainfall, Temperature, and Humidity are physical factors that affect DHF, this was conveyed in the study [21] by taking secondary data in Semarang City in 2006 -2015 it was found that rainfall, temperature, and humidity had an effect on the number of DHF cases in Semarang. Semarang City (p < 0.05).…”
Section: Factors That Affect Dhfmentioning
confidence: 90%
“…The size of the human population as a host is expressed as N h = S h +I h +R h and the size of the mosquito population as a vector is expressed as Nv = Sv+Iv. Likewise in the SIR model [21] vaccine images are given to strengthen immunity from viral attacks.…”
Section: Optimal Control On Dhf Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saat ini morbiditas (angka kesakitan) diare di Indonesia mencapai 195 per 1000 penduduk dan angka ini merupakan yang tertinggi di antara negara-negara di Asean. Diare juga masih merupakan masalah kesehatan yang penting di Indonesia (2).…”
Section: Pendahuluanunclassified
“…Dimana pada tahun 2014 kasus tertinggi adalah di Bali (204,22 per 100.000 penduduk), Kalimantan Timur (135,46 per 100.000 penduduk) dan Kalimantan Utara (128,51 per 100.000 penduduk). (Lahdji & Putra, 2017) Salah satu pengendalian DBD di Indonesia yang dapat dilakukan adalah kegiatan pemberantasan sarang nyamuk (PSN).…”
Section: Pendahuluanunclassified